Implementasi Manajemen Humas dalam Peningkatan Mutu Layanan Berbasis Digital di SMP Islam Terpadu Al-Hijrah Deli Serdang - Mesiono Mesiono; Yusuf Hadijaya; Abdillah Abdillah; Suwandi Suwandi (JURNAL LENSA MUTIARA KOMUNIKASI, 2021)
This study uses qualitative research, the subject of this research is public relations management in SMP IT Al-Hijrah Deli Serdang in shaping the quality of digital-based education services. Digitalization systems in improving the quality of education services such as using virtual accounts in the process of paying school fees. The role of public relations in improving the quality of digitalization-based education at SMP IT Al-Hijrah Deli Serdang . Already implementing a digitalization system in conveying information about student development, student financial administration, attendance, student and teacher attendance and so on The policies formulated by SMP IT Al-Hijrah Deli Serdang related to the implementation of public relations management in improving digitalization-based education services have been formulated properly and accordingly the needs of stakeholders are also realized through various strategic programs. Although overall it has not yet fulfilled the stages of good policy formulation. Public relations management has a role in the dissemination of policies and commitment in implementing the ability to improve the quality of education based on digitalization at SMP IT Al-Hijrah Deli Serdang , the management planning process in improving digitalization-based education services is considered sufficient. good and cooperative by involving related elements. The role of public relations management in improving the quality of digitalization-based education services still tends to be a reactive formal institution but less progressive so that the organization has not been able to accelerate the process of implementing digitalization-based education quality services at SMP IT Al-Hijrah Deli Serdang so that the image of public relations management in improving the quality of education services is still lacking. and due to a lack of commitment from all stakeholders at SMP IT Al-Hijrah Deli Serdang .